KEANEKARAGAMAN DAN POTENSI JENIS VEGETASI PENYUSUN HUTAN TEMBAWANG AMPAR DI DESA CEMPEDAK KECAMATAN TAYAN HILIR KABUPATEN SANGGAU - pin, Ri; Astiani, Dwi; Latifah, Siti (Universitas Tanjungpura, 2014)
Tembawang Ampar is located at the Village of Cempedak, District of Tayan Sanggau. Human activities to use and manage of this tembawang affected the sustainability of the forest ecosystem. The objectives of this study is to determine the diversity, the potency and the most dominant species of tembawang Ampar forest. The research was conducted by applying survey method with stratified sampling. Within each stratum (1. dominated by fruit tree; 2. rubber; and 3. apik), we used survey technique with a combination of line transects method with systematic plot samplings). Our research indicated that there were 97 species of vegetation registered, which were grouped into 34 family. The analysis of the Shannon-Wiener diversity index showed that species diversity of forest vegetation within in the tembawang Ampar dominated by rubber and Apik plant is lower than fruit tree cover. The diversity Indexes of rubber and apik plat were H '<1, the while the area of ​​fruit trees showed diversity Index between1 ≤ H '≤ 3. The most dominant species and the greatest potency in the tembawang Ampar forest is rubber plant (Hevea brasilliensis Will ex A. Juss) of family Euphorbiaceae. Keywords: Species diversity, dominant species,, tembawang, Ampar forest sustainability